PENERAPAN METODE ROOT CAUSE ANALYSIS (RCA) UNTUK MENENTUKAN AKAR PENYEBAB KELUHAN KONSUMEN - Destree Christian; Agung Sutrisno; Jefferson Mende (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2018)
The development of the business world in Indonesia, today has shown an encouraging direction. It can be seen from the proliferation of various forms of business entities engaged in the field of goods and services both small and large scale. One of them is wedding organizer service. Wedding organizer provider company must be able to provide maximum service to increase consumer satisfication.This research is related to the application of the Root Cause Analysis (RCA) method in determining the factors that influence the low level of customer satisfaction in wedding organizer service providers.The purpose of this study is to determine the important factors that cause the low levels of customer satisfaction and provide suggestions for improving the performance of service providers in wedding organizers. This analysis uses SERVQUAL variables which contain service quality dimensions such as tangibles, reliability, empathy, responsiveness, and assurance.The results of research conducted using these 14 variables, show that there are three factors that cause low levels of customer satisfaction, they are not acting fast when consumers need (complaints given by consumers are not immediately responded to), not able to provide information according to customer needs (no service list), not having the availability of interesting event photobooths ( no availability of photographer at photobooth place, and five improvement proposals for wedding organizer service providers, such as procurement of communication equipment, assigning tasks based on mastered fields, scheduling more carefully, more thoroughly in providing information, paying more attention to concept and theme of the event according to the consumer wishes.Keywords: Wedding Organizer, SERVQUAL, Consumer Satisfaction, Fault Tree.